A liberdade nomeada: leituras de Cecília Meireles para Cânticos - Bezerra, Emília Passos de Oliveira (2007)
The dissertation examines the work Songs, Cecilia Meireles, highlighting the historical context-cultural, ideological and artistic of the twentieth century, from the close relationship of literature produced by the poet with the mysticism of the philosophies of the East, in particular, Buddhism, with the mystical poetry of the Indian poet Rabindranath Tagore and the speeches of peace Mahatma Gandhi and Vinoba Bhave. The work of the poetic corpus, still uses to support the writer Complete Poetry, the critical study conducted by Amy Zagury, "Cecília Meireles: news biographical, critical study, anthology, literature, discography, the score," and in the testimony of letters, interviews, books and chronic prefaciados as princiapal refuge. Using the methods descriptive, analytical, interpretive-comparison, the search is divided into five stages, where: "Initial considerations", "The twentieth century", "Songs - named Freedom," "The Bilbioteca way" and, finally, as a conclusion, "The uniqueness of mystical corner."